PENERAPAN KANTIN SEHAT “BERSERI” DI SD NEGERI WULUHADEG SANDEN BANTUL - Indriana Dewi; Mahilda Dea Komalasari (Jurnal PGSD Indonesia, 2023)
The aims of this research are (1) to identify the implementation of the "BERSERI" healthy canteen at Wuluhadeg State Elementary School, (2) to determine the development of a healthy canteen implemented at Wuluhadeg State Elementary School, (3) to find out the institutional role for a healthy canteen, especially at Wuluhadeg State Elementary School. The method used is a qualitative method. The research subjects were school principals, teachers, canteen sellers, and students at Wuluhadeg State Elementary School. Data collection techniques are observation, interviews and documentation. The data analysis used is the Miles and Huberman model. Checking the validity of the data uses source triangulation and technical triangulation. The results of the research indicate that (1) Wuluhadeg Public Elementary School has implemented a healthy school canteen that meets the criteria for a healthy canteen. The BERSERI healthy canteen serves food and drinks that are healthy and safe for sale, such as self-processed food/drinks that do not contain preservatives, borax or other dangerous substances. (2) Development of a healthy canteen includes the design of healthy canteen services, implementation of healthy canteen services, healthy canteen facilities and infrastructure, supervision of healthy canteen services, as well as efforts to improve healthy canteens, (3) The institutional role of healthy canteens includes the role of students, canteen sellers, school principals, teachers and parents. The most important role of students in the BERSERI healthy canteen is as consumers, maintaining the cleanliness of the canteen and implementing PHBS habits. Meanwhile, the role of the canteen seller is to provide food that is kept clean and healthy. The role of the school principal is as person in charge, protector, guide and resource regarding healthy canteens. The teacher's role is to carry out inspection and supervision of food sold in the canteen. And parents play a role in providing advice to children regarding healthy food, providing criticism and suggestions for the improvement of the school canteen